Toxicological characterization of ZnO nanoparticles in malignant and non‐malignant cells. (18th November 2017) - Moratin, Helena; Scherzad, Agmal; Gehrke, Thomas; Ickrath, Pascal; Radeloff, Katrin; Kleinsasser, Norbert; Hackenberg, Stephan
Abstract : The increasing usage of zinc oxide nanoparticles (ZnO‐NPs) in industrial applications as well as in consumer products raises concern regarding their potential adverse effects to a greater extend. Numerous studies have demonstrated toxic properties of NPs, however there is still a lack of knowledge concerning the underlying mechanisms. This study was designed to systematically investigate cytotoxicity, apoptosis, cell cycle alterations, and genotoxicity induced by ZnO‐NP. Moreover, it was an aim of the investigations to specify the diverse effects of nanoparticle exposure in malignant in comparison with non‐malignant cells. Therefore, human head and neck squamous cell carcinoma‐derived FaDu cells were incubated with 4–20 µg/ml of ZnO‐NPs for 1–48 hr and tested for cell viability, cell cycle alterations, apoptosis and caspase‐3 gene expression as a sensitive marker of molecular apoptotic processes with regard to time‐ and dose‐dependent effects. Human mesenchymal bone marrow stem cells were used as non‐malignant representatives to examine oxidative stress‐related genotoxicity. Results showed a significant reduction in cell viability as well as dose‐ and time‐dependent increase of apoptotic cells following nanoparticle treatment. Likewise, caspase‐3 gene expression enhanced already before first apoptotic cells were detectable. It could be observed that doses that were cytotoxic in tumor cells did not reduce viability in stem cells. However, the same concentrations already induced significant DNA damage. The findings of the study suggest to keep a more critical eye on the use of nanoparticles as anti‐cancer agents. Yet, additional in vivo studies are needed to assess safety concerns for consumers and patients. Environ. Mol. Mutagen. 59:247–259, 2018. © 2017 Wiley Periodicals, Inc.